Response mechanisms of bacterial communities and nitrogen cycle functional genes in millet rhizosphere soil to chromium stress - Bai, Xue; Li, Yvjing; Jing, Xiuqing; Zhao, Xiaodong; Zhao, Pengyu (Frontiers in Microbiology, 2023)
A growing amount of heavy metal contamination in soil harms crops and disturbs the ecosystem’s equilibrium, whereas the microbial community is essential to the cycling of nutrients in ecosystems. In this study, samples were taken prior to Cr stress (CK) and 6 h and 6 days after Cr stress (Cr_6h, Cr_6d) in laboratory experiments. High-throughput sequencing revealed trends in the structure and diversity of the soil bacterial communities, and real-time fluorescence quantitative polymerase chain reaction (qPCR) was used to analyze trends in the functional genes involved in the nitrogen cycle (nitrification [AOA-amoA, AOB-amoA], denitrification [narG, nirK], and nitrogen fixation [nifH]). The findings showed that (1) the composition structure of the soil bacterial community changed considerably in the time series of Cr stress; α-diversity showed a phase transition characteristic from stress to stability (Shannon: 6.09, 5.93, 6.05; Simpson: 0.0068, 0.0078, 0.0068, P<0.05). (2) With an overall rising tendency, the abundance of the nitrogen cycle functional genes (AOA-amoA and AOB-amoA) decreased considerably before increasing (P<0.05), and α-diversity dramatically declined (Simpson: 0.794, 0.793, 0.795, P<0.05). (3) The redundancy analysis (RDA) and permutational multivariate analysis of variance (PERMANOVA) tests results showed that the soil physicochemical properties were significantly correlated with the nitrogen cycle functional genes (r: 0.4195, P<0.01). Mantel analysis showed that N, K and EC were significantly correlated with nifH (P= 0.006, 0.008, 0.004), and pH was highly significantly correlated with nifH (P=0.026). The PLS-ME (partial least squares path model) model further demonstrated a significant direct effect of the soil physicochemical properties on the nitrogen cycling functional genes. As a result, during the time series of Cr stress, both the composition and diversity of the bacterial community and the functional genes involved in the nitrogen cycle in the soil changed considerably. However, the influence of the soil physicochemical properties on the functional genes involved in the nitrogen cycle was greater than that of the bacterial community, and Cr stress mostly affected nitrification. This research has significant practical ramifications for understanding the mechanisms of microbial community homeostasis maintenance, nitrogen cycle response mechanisms, and soil remediation in heavy metal–contaminated agricultural soils.